2016
DOI: 10.1590/s1519-99402016000400009
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura de covariância para características de carcaça e tamanho corporal com medidas repetidas em ovinos de diferentes grupos genéticos

Abstract: RESUMO Objetivou-se avaliar a influência de efeitos ambientais sobre medidas corporais, peso e características de qualidade de carcaça, com estrutura de mensurações repetidas no tempo, em ovinos de diferentes grupos genéticos. Foram realizadas coletas do nascimento aos 180 dias de idade, durante os anos de 2012 e 2013, em 92 cordeiros de 3 grupos genéticos, sendo 29 da raça Santa Inês, 43 mestiços Dorper x Santa Inês e 20 mestiços Dorper x Morada Nova, pertencentes a dois rebanhos. Foram mensuradas área e prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The lack of effect on carcass characteristics among efficiency groups was expected, because animals were slaughtered with similar BW (P>0.05). Weight, yield, and size of animals at slaughter have a positive correlation with carcass characteristics (Cyrillo et al, 2012;Santos et al, 2016b). Our results corroborate previous findings by Nascimento et al (2016), who evaluated HCW and HCY of Nellore calves and found no significant differences among RIG groups.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of effect on carcass characteristics among efficiency groups was expected, because animals were slaughtered with similar BW (P>0.05). Weight, yield, and size of animals at slaughter have a positive correlation with carcass characteristics (Cyrillo et al, 2012;Santos et al, 2016b). Our results corroborate previous findings by Nascimento et al (2016), who evaluated HCW and HCY of Nellore calves and found no significant differences among RIG groups.…”
Section: Discussionsupporting
confidence: 92%
“…Defeathered, semieviscerated, and eviscerated carcass yields were higher in this study than in our previous study, at 80.70, 76.27, and 70.34%, respectively ( Bai et al, 2022 ). Animal weight, yield, and size at slaughter are all positively connected to carcass traits ( Santos et al, 2016 ). The trends in liver yield with respect to RFI were consistent with earlier findings by Fathi et al (2019) and Gabarrou et al (1998) , who found that RFI was genetically and phenotypically associated with lower heart, liver, and gizzard yields.…”
Section: Resultsmentioning
confidence: 99%